Bipolar Current Collectors of Carbon Fiber Reinforced Polymer for Laminates of Structural Battery - Byeong Jun So; Yusu Han; Gilyong Shin; Hyeong Jun Kim; Juhwan Lee; Jeon, Jei Gyeong; Tae June Kang (한국정밀공학회, 2025)
Structural batteries are multi-functional composites that combine the functions of energy storage and mechanical load support. Bipolar current collectors allow batteries to be electrically stacked in series, increasing power and energy density while maintaining device integrity. In this study, bipolar current collectors (CCs) were fabricated in a sheet of carbon fiber fabric impregnated with an epoxy resin using vacuum-assisted resin transfer molding. Pressure was applied during the resin curing process to improve the mechanical properties of the bipolar CCs. The CC produced at an optimum pressure of 6.0 bar showed excellent mechanical properties, with a tensile strength and modulus of 833 MPa and 63.6 GPa, respectively, and exhibited a low through-plane resistivity of 4.9 Ω cm, facilitating efficient electron transfer between the stacked batteries. The electrochemical stability of the CCs was excellent over a wide voltage window of 2.45 V, even under harsh acidic and alkaline electrolyte conditions. To demonstrate the scalability of the device in terms of power and energy density, zinc-ion based structural batteries were fabricated by alternately stacking the batteries using the CC. The implementation of the CC presented here could lead to a significant improvement in the performance by reducing the weight and volume of the device.